Institutional Change in Brazilian Public Administration:The case of the Ombudsman’s Offices in Federal Regulatory Agencies - Miranda, Luciana de Oliveira; Calmon, Paulo Du Pin (Organizações & Sociedade, 2016)
This research study seeks to understand the process for the institutionalization of Ombudsman’s Offices in federal regulatory agencies. It is based on a constructivist research strategy and examines five case studies. The theoretical framework is based on the Theory of Institutional Change advocated by Thelen and colleagues (2005 and 2010), associated with Lawrence and Suddaby’s (2006) types of institutional work. The result of this analysis proves the existence of proactive actions by agents of change who belong – or belonged – to the Ombudsmen teams involved in the study.